2001
DOI: 10.2225/vol14-issue1-fulltext-2
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production from sweet sorghum juice under very high gravity conditions: Batch, repeated-batch and scale up fermentation

Abstract: Batch ethanol fermentations from sweet sorghum juice by Saccharomyces cerevisiae NP 01 were carried out in a 500 ml air-locked Erlenmeyer flask under very high gravity (VHG) and static conditions. The maximum ethanol production efficiency was obtained when 9 g l -1 of yeast extract was supplemented to the juice. The ethanol concentration (P), productivity (Qp) and yield (Yp/s) were 120.24 ± 1.35 g l -1, 3.01 ± 0.08 g l -1 h -1 and 0.49 ± 0.01, respectively. Scale up ethanol fermentation in a 5-litre bioreactor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 11 publications
(13 reference statements)
3
30
0
1
Order By: Relevance
“…Lower ethanol concentration and productivity in batches 2 to 20 might be due to lower yeast cell concentrations in the fermentation broth compared with those in the first batch. These results were similar to those of Ariyajarearnwong et al [21], Chen et al [36] and Nuangpeng et al [28]. They demonstrated that the initial cell concentration affected ethanol concentration and productivity in repeated-batch fermentation using free yeast cells.…”
Section: Repeated-batch Ethanol Fermentationsupporting
confidence: 89%
See 2 more Smart Citations
“…Lower ethanol concentration and productivity in batches 2 to 20 might be due to lower yeast cell concentrations in the fermentation broth compared with those in the first batch. These results were similar to those of Ariyajarearnwong et al [21], Chen et al [36] and Nuangpeng et al [28]. They demonstrated that the initial cell concentration affected ethanol concentration and productivity in repeated-batch fermentation using free yeast cells.…”
Section: Repeated-batch Ethanol Fermentationsupporting
confidence: 89%
“…Then, they were mixed thoroughly to obtain the final total sugar concentration of 280 g·L of yeast extract [8,28] were also prepared as the control treatments. For repeated-batch ethanol fermentation, the concentrated juice was diluted with distilled water to the desired total sugar concentration and used as the EP medium.…”
Section: Ethanol Production Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…It is found to have protective effects either on growth and fermentation or cell viability, which stimulate the fermentation rate and ethanol production [12,23]. Laopaiboon et al [23] and Nuanpeng et al [24] showed that 9 g L −1 of yeast extract promoted batch ethanol production from sweet sorghum juice containing 280 g L −1 of total sugar and sugar utilization was almost complete under the agitation rate of 100 rpm without aeration. However, a very high initial yeast cell concentration (1 × 10 8 cells mL −1 ) was required.…”
Section: Introductionmentioning
confidence: 99%
“…Besides sugar and nitrogen content, fermentation performance of sweet sorghum juice can also be affected with processing parameters and bioreactor configuration. Nuanpeng et al (2011) observed in a repeated-batch study that very high gravity (VHG) fermentation is a good alternative to produce high ethanol concentrations from sweet sorghum juice when an adequate level of yeast cell concentration, nitrogen, and agitation are used. On the other hand, Laopaiboon et al (2007) reported better results in fed-batch fermentation compared to batch configuration, in terms of ethanol concentration and product yield but not in productivity (measured as grams of ethanol generated/L/hr).…”
Section: Ethanol Fuel From Sweet Sorghum Juicementioning
confidence: 99%